Does increasing active warm-up duration affect afternoon short-term maximal performance during Ramadan? - Hana Baklouti; Asma Aloui; Hamdi Chtourou; Walid Briki; Anis Chaouachi; Nizar Souissi (PLoS ONE, 2015)
AIM:The purpose of this study was to examine the effect of active warm-up duration on short-term maximal performance assessed during Ramadan in the afternoon. METHODS:Twelve healthy active men took part in the study. The experimental design consisted of four test sessions conducted at 5 p.m., before and during Ramadan, either with a 5-minute or a 15-minute warm-up. The warm-up consisted in pedaling at 50% of the power output obtained at the last stage of a submaximal multistage cycling test. During each session, the subjects performed two vertical jump tests (squat jump and counter movement jump) for measurement of vertical jump height followed by a 30-second Wingate test for measurement of peak and mean power. Oral temperature was recorded at rest and after warming-up. Moreover, ratings of perceived exertion were obtained immediately after the Wingate test. RESULTS:Oral temperature was higher before Ramadan than during Ramadan at rest, and was higher after the 15-minute warm-up than the 5-minute warm-up both before and during Ramadan. In addition, vertical jump heights were not significantly different between the two warm-up conditions before and during Ramadan, and were lower during Ramadan than before Ramadan after both warm-up conditions. Peak and mean power were not significantly different between the two warm-up durations before Ramadan, but were significantly higher after the 5-minute warm-up than the 15-minute warm-up during Ramadan. Moreover, peak and mean power were lower during Ramadan than before Ramadan after both warm-up conditions. Furthermore, ratings of perceived exertion were higher after the 15-minute warm-up than the 5-minute warm-up only during Ramadan. CONCLUSION:The prolonged active warm-up has no effect on vertical jump height but impairs anaerobic power assessed during Ramadan in the afternoon.